2022
DOI: 10.1108/mbe-12-2021-0151
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable value creation and organizational performance in industrial manufacturing companies

Abstract: Purpose This study aims to analyze the influence of sustainable value creation (composed of social, economic and environmental dimensions) on organizational performance in Colombian industrial manufacturing companies. Design/methodology/approach This study had a sample of 1,572 companies belonging to the Colombian manufacturing industrial sector. These companies were consulted by the survey of technological development and innovation in the manufacturing industry EDIT IX. For this study’s purpose, a model wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Managing environmental assets benefits the manufacturing company's fiscal and societal success (Torrent-Sellens et al, 2023). The corresponding social, economic, and environmental mechanisms significantly, favourably and greatly add to the development of sustainable value and success for businesses (Acosta-Prado et al, 2023). The statistical analysis of the study of Salmanzadeh-Meydani et al (2023) demonstrates a direct relationship between ES and ENP.…”
Section: Environmental Sustainability (Ens) and Financial Performance...mentioning
confidence: 98%
See 1 more Smart Citation
“…Managing environmental assets benefits the manufacturing company's fiscal and societal success (Torrent-Sellens et al, 2023). The corresponding social, economic, and environmental mechanisms significantly, favourably and greatly add to the development of sustainable value and success for businesses (Acosta-Prado et al, 2023). The statistical analysis of the study of Salmanzadeh-Meydani et al (2023) demonstrates a direct relationship between ES and ENP.…”
Section: Environmental Sustainability (Ens) and Financial Performance...mentioning
confidence: 98%
“…, 2023). The corresponding social, economic, and environmental mechanisms significantly, favourably and greatly add to the development of sustainable value and success for businesses (Acosta-Prado et al. , 2023).…”
Section: Development Of the Hypothesesmentioning
confidence: 99%
“…By employing energy-efficient technologies, refining operational processes and encouraging responsible consumption, companies can markedly reduce operational costs, boosting their profitability (Acosta-Prado et al, 2022;Fu et al, 2022). Furthermore, through waste minimization and material reuse, organizations lessen their reliance on potentially costly or price-volatile raw materials (Danso et al, 2020).…”
Section: Internal Sustainability Implementation (Isi) and External Su...mentioning
confidence: 99%
“…Enforcing sustainability standards across the supply chain safeguards organizations from potential financial burdens like environmental fines, product recalls or reputation loss due to supplier non-compliance (Govindan et al, 2020). Moreover, equipping suppliers with sustainability knowledge can spark cost-efficient innovations, culminating in mutual cost benefits for themselves and their partners (Acosta-Prado et al, 2022;Fu et al, 2022). Collaborative efforts between companies and their suppliers can lead to the co-creation of optimized production methods, minimized resource use and risk reduction, all contributing to substantial economic gains (Wong et al, 2020;Melander and Pazirandeh, 2019).…”
Section: External Sustainability Implementation (Esi) and Sustainabil...mentioning
confidence: 99%
“…The work of Acosta-Prado et al (2022) has indicated that sustainable business practices, leading to sustainable value creation, has a significant and positive influence on organizational performance. Columbian industrial manufacturing firms have evidenced a sustained improvement in terms of organizational performance when adopting practices that look to promote social and environmental value creation alongside firm profit.…”
Section: Columbian Sustainable Manufacturingmentioning
confidence: 99%